How far are we? Information from the three decades of ethnomedicinal studies in Thailand - Phumthum, Methee (Ethnobiology and Conservation, 2020)
Ethnobotany has been an academic discipline for more than a century. In Thailand, it was introduced into academia only 30 years ago, but the study has been carried on extensively. To analyze the number of ethnomedicinal reports based in Thailand and guide the design of future studies. The details include studied villages and ethnic groups from publications appearing during the course of the last 30 years. Ethnomedicinal reports were collected from online databases – Google Scholar, Scopus, PubMed – and university libraries in Thailand. The other literature sources were Thai journals and the website of the Thai Library Integrated System. The period of publications ranges from 1990 to 2019. During this period, a total of 146 publications (student theses, journal articles, scientific reports, and a book) were published from 32 universities and research institutes in Thailand. The publications revealed records of plants used by 223 villages in 25 ethnic groups overall in Thai regions. Although ethnobotany started in Thailand after 70 years of a continuous track record in other parts of the world, the success in Thailand is reflected in the high number of studies and studied villages. However, more studies need to be done in many other villages and ethnic groups in the country before the subject can be considered well broached.